1995
DOI: 10.1017/s0016756800021245
|View full text |Cite
|
Sign up to set email alerts
|

Terrane geochemistry contrasts across the Iapetus Suture in Ireland

Abstract: In the Irish Caledonides, volcanism has been significant in terrane identification and in reconstructions of the Appalachian/Caledonian orogen. Crucial to these reconstructions is the recognition of ocean margins using obducted ocean floor relics (ophiolites) and supra-subduction zone volcanic assemblages. The volcanic rocks provide much evidence for the affinity of a terrane, however, by analogy with present day examples, the ocean floor sediments may provide the best way of tracing both ocean-floor magmatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
2
0
0
Order By: Relevance
“…Geochemical analyses of shale samples from selected belts within each terrane by Ryan et al (1995) support our interpretation. The analyses showed that the shales from the central and northern belts (LDM, Fig.…”
Section: Discussion a N D I N T E R P R E Tat I O Nsupporting
confidence: 80%
See 1 more Smart Citation
“…Geochemical analyses of shale samples from selected belts within each terrane by Ryan et al (1995) support our interpretation. The analyses showed that the shales from the central and northern belts (LDM, Fig.…”
Section: Discussion a N D I N T E R P R E Tat I O Nsupporting
confidence: 80%
“…1) have low maturity, whereas those from southern part and the Leinster belt have relatively high maturity. In our study, although it is difficult to find exact spatial correspondence with the litho-geochemical analysis of Ryan et al (1995), the change in resistivity in the western part of Ireland is attributed to the similar processes, as discussed similarly by Korja et al (2008). Figs 8 and 9 show a prominent conductor in central Ireland at upper mantle depths of 60 km and deeper on profile V below the stations 105-107, that is not seen beneath the other profiles.…”
Section: Discussion a N D I N T E R P R E Tat I O Nsupporting
confidence: 70%